PENGAWASAN KETENAGAKERJAAN DI BIDANG KESEJAHTERAAN - Totok Tumangkar (Fakultas Hukum Universitas 17 Agustus (UNTAG) Semarang, 2020)
The essence of labor inspection is the activity of supervising and enforcing the implementation of laws and regulations in the manpower sector. The relationship between supervision and welfare is an inseparable pair, if you expect a maximum achievement. In terms of labor inspection it is not enough to be limited to supervision, but for the continuity of the realization of the supervision, a systematic, recorded and integrated supervision must be carried out, so that the results of the inspection must be applied in the world of work and be effective in improving the welfare of workers. and enforce the implementation of laws and regulations in the manpower sector, so that in this effort the government also establishes a labor inspection work unit from the top to the lowest as stipulated in Law Number 13 of 2003. Employees of the Labor Inspection, even ministers also have duties in this field. Protection between labor inspection and work success is always carried out in an integrated, coordinated and integrated inspection system which includes the work unit of labor inspection, labor inspectors and labor inspection procedures.